Design and construction of a quad-pole coupling device for partial discharge tests - Marukatat, Nattapon; Kunakorn, Anantawat; Yutthagowith, Peerawut (My University, 2017)
This paper presents design and construction of a quad-pole coupling device which is used for measurement of PD signal and AC voltage as the conventional partial discharge testing according to IEC 60270[1]. The developed coupling device is capable to measure AC voltage at frequencies of 50 Hz and 200 Hz. Lower limit and Upper limit frequencies of the developed coupling device are 30 kHz and 20 MHz, respectively. The remarkable feature of the developed coupling device has the accuracy in PD signal measuring and the ability in eliminating noise signal such as unwanted AC signal at PD measuring point and interference signal. Therefore, in the design procedure based on OrCAD computer program, two main parts being the AC signal measuring part and the PD signal measuring part are considered. In the AC signal measuring part, the proper impedance was chosen to achieve appropriate voltage divide ratio and accuracy in PD signal measuring. In the coupling device, voltage surge protective device was installed to protect the PD measuring part. In PD signal measuring part, the value of the components in PD signal measuring circuit must be chosen properly to achieve the determined upper and lower limit frequencies and consider the value of the matching resistance. In this part, noise signal elimination must be considered to gain less effect to PD signal, otherwise the PD signal waveform will distort. From this intensive study, the coupling device circuits were designed and constructed and then, they were tested at 50 Hz and 200 Hz AC Voltage supply. The results of the developed coupling device are compared to that of the reference coupling device in the high voltage laboratory of King Mongkut's Institute of Technology Ladkrabang. The developed coupling device can be used in conventional PD testing according to IEC 60270. The comparisons of the simulated and experimental results show that the performance of the developed coupling devices as same as the reference coupling device.
Keywords: Coupling device; IEC 60270; Partial discharge detection